2018
DOI: 10.1186/s40734-018-0074-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of vitamin D supplementation and clinical outcomes in a large cohort of early Parkinson’s disease

Abstract: BackgroundVitamin D (VitD) deficiency is common in Parkinson’s disease (PD) and has been raised as a possible PD risk factor. In the past decade, VitD supplementation for potential prevention of age related conditions has become more common. In this study, we sought to characterize VitD supplementation in early PD and determine as an exploratory analysis whether baseline characteristics or disease progression differed according to reported VitD use.MethodsWe analyzed data from the National Institutes of Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…A longitudinal study which enrolled 1741 newly diagnosed PD subjects divided into four groups according to supplementation (no supplementation; multivitamin supplements; multivitamin plus vitamin D; only vitamin D) failed to identify any differences in disease progression across all groups after three years. In fact, no changes in the main outcome measures (Unified Parkinson’s Disease Rating Scale (UPDRS), routine daily activities, ADL, Parkinson’s disease questionnaire (PDQ), symbol digit modalities test (SDMT), or levodopa equivalent dose (LED) were detected at the end of follow-up [ 110 ].…”
Section: Vitamin D Supplementation In Parkinson’s Diseasementioning
confidence: 99%
“…A longitudinal study which enrolled 1741 newly diagnosed PD subjects divided into four groups according to supplementation (no supplementation; multivitamin supplements; multivitamin plus vitamin D; only vitamin D) failed to identify any differences in disease progression across all groups after three years. In fact, no changes in the main outcome measures (Unified Parkinson’s Disease Rating Scale (UPDRS), routine daily activities, ADL, Parkinson’s disease questionnaire (PDQ), symbol digit modalities test (SDMT), or levodopa equivalent dose (LED) were detected at the end of follow-up [ 110 ].…”
Section: Vitamin D Supplementation In Parkinson’s Diseasementioning
confidence: 99%
“…This study shows an inverse relationship between VitD level and risk and severity of PD in 2866 PD patients [94]. There is a limited response of VitD supplementation (≥400 IU/day) in early PD patients, and this warrants further study to justify its therapeutic potential [95]. Therefore, more cohort studies of early and late PD patients are needed to illuminate the connection between VitD and PD further.…”
Section: Vitamins Based Clinical Studies In Parkinson's Diseasementioning
confidence: 85%
“…A large randomised multicentre, double-blind, placebo-controlled study of VitD supplementation (≥400 IU/day) given to patients with early PD (<5 years of PD disease) showed that patients taking VitD supplementation did not alter early disease progression, but continued supplementation with VitD still had the potential to reduce the incidence of disability associated with bone health, as osteoporosis is more common in PD and the risk of falls and risk of fracture increases with disease progression. These data may be useful in designing studies to test the effects of vitamin D supplementation over a longer time frame ( Luthra et al, 2018 ). Therefore, more cohort studies of early and late PD patients are needed to illuminate the connection between VitD and PD further.…”
Section: Discussionmentioning
confidence: 99%